PENGARUH VALUE CLARIFICATION TECHNIQUE (VCT) TERHADAP PENINGKATAN MORAL SISWA KELAS VIII DI SMP NEGERI 37 MEDAN - Della Puspita; Sri Yunita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the Effect of VCT on the Improvement of Morale of VIII Grade Students at SMP Negeri 37 Medan. Based on the student questionnaire about morale at school, the background of this study is due to the presence of students who rarely help and respect teachers, lack empathy for friends who are sad, students who often say bad words, students who often tease, fight, cheat, and lie. This study uses an experimental research type with Pre-test Post-test Control Group Design. The population in this study was all VIII grade students at SMP Negeri 37 Medan with the sample used was Non Probability with Purposive Sampling technique and the sample was only two classes totaling 58 people, where class D as the experimental group and class F as the control group. Researchers used data collection instruments in the form of observation, questionnaires and documentation. The techniques used for data processing were obtained, processed, and analyzed using the application program Statistical Package for the Social Sciences (SPSS) 26.0. The results showed that VCT had an effect on improving the morale of students in VIII grade students at SMP Negeri 37 Medan. The N-Gain results for students' morale using the experimental class were 67%, while the morale of students in the control class was 42%. Based on these N-Gain results, it can be concluded that the use of VCT in improving student morale is quite effective.